Improving Poem Writing Skill Through Smart Ludo Media For Grade IV Students - Kara, Raka Bagas; Fathurohman, Irfai; Fajrie, Nur (Jurnal Ilmiah Sekolah Dasar, 2020)
The low learning outcomes of students' writing skills were the main reason this research was conducted. It happens because the learning model that applied is less effective so it has not been able to optimally hone students writing skills. This study aims to determine the application of smart ludo media to improve poem writing skills in elementary students. This type of research is a classroom action research subject. This research lasted for two cycles, where each cycle consisted of four stages including planning, implementing, observing, and reflecting. Data collection techniques used tests, interviews, observation, and documentation. The results showed that there was an increase in students’ skills in writing poems through smart ludo media. The improvement of writing poetry skills in the first cycle obtained a classical completeness value of 73.91% and the second cycle obtained a classical completeness value of 91.30%. based on the results of classroom action research that has been carried out on fourth-grade elementary school students, it can be concluded that there is a positive effect of the application of smart ludo media on improving student learning outcomes in poem writing skills. The results of this study can be used by the teacher as a tool in conveying learning to students and it can be a reference for research using similar research objects.